2019
DOI: 10.1093/mutage/gez044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 2-acetylaminofluorene and its genotoxic metabolites on DNA adduct formation and DNA damage in 3D reconstructed human skin tissue models

Abstract: In vitro genotoxicity assays utilising human skin models are becoming important tools for the safety assessment of chemicals whose primary exposure is via the dermal route. In order to explore metabolic competency and inducibility of CYP450 activating enzymes, 3D reconstructed human skin tissues were topically treated with 2-acetylaminofluorene (2-AAF) and its genotoxic metabolites, N-hydroxy-2-acetylaminofluorene (N-OH-2-AAF) and N-hydroxy-2-aminofluorene (N-OH-2-AF), which primarily cause DNA damage by formi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…The level of cytotoxicity was slightly below the threshold limits in this experiment; however, based on the clear increase in DNA damage in both cell types, 2-AAF was correctly classified as positive. This result is supported by recent data published by Downs et al ( 48 ), which showed that a reactive metabolite (as demonstrated by DNA adduct formation) accumulates with the multiple treatment protocol utilised in this validation study, leading to positive responses in the RS Comet assay. Importantly, 2-AAF is a pro-mutagen, the known metabolic pathways of which involves NAT and CYP1A2 and leads to the formation of genotoxic metabolites ( 52 , 53 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The level of cytotoxicity was slightly below the threshold limits in this experiment; however, based on the clear increase in DNA damage in both cell types, 2-AAF was correctly classified as positive. This result is supported by recent data published by Downs et al ( 48 ), which showed that a reactive metabolite (as demonstrated by DNA adduct formation) accumulates with the multiple treatment protocol utilised in this validation study, leading to positive responses in the RS Comet assay. Importantly, 2-AAF is a pro-mutagen, the known metabolic pathways of which involves NAT and CYP1A2 and leads to the formation of genotoxic metabolites ( 52 , 53 ).…”
Section: Resultssupporting
confidence: 90%
“…It is likely that the Phase I activation capacity of the skin models is not sufficient to produce enough DNA reactive metabolite(s) to cause an increase in strand breaks strong enough for a significant effect versus control levels. This assumption is also supported by the APC-induced accumulation of DNA adducts in 2-AAF treated skin models ( 48 ). While the sensitivity was greatly enhanced, the specificity of the RS comet assay was reduced slightly.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…In skin, there is evidence for metabolism of topically-applied 2-AAF in human skin explants ( 28 ) and a weak, but statistically significant and reproducible increase in DNA damage was detected in the RS Comet assay ( 1 ). In another study, multiple treatments of RS tissues with 2-AAF led to the induction of metabolic enzymes, generation of reactive metabolites and formation of DNA adducts, which was associated with a significant response in the RS Comet assay, but not in the RSMN assay ( 29 ). It was also demonstrated that the DNA damage caused by direct treatment with known genotoxic metabolites of 2-AAF, N -hydroxy-2-acetylaminofluorene and N -hydroxy-2-aminofluorene, was more efficiently detected in the RS Comet assay than in the RSMN assay ( 29 ).…”
Section: Results Of Rsmn Assay Validation Phases 2a–2dmentioning
confidence: 99%
“…No exposure. Static environment (Petrova et al 2016 ) Human skin equivalent (HSE) Primary cells/tissues Higher barrier property than RHE model (thus more suitable for permeation studies) Addition of fibroblasts essential for wound healing studies Culture of 3 weeks was demonstrated Approved by OECD for several endpoints Show good metabolic capacity Acceptance criteria for OECD guideline available Still lower barrier property than in vivo Measured toxic effects of doxorubicin in pumpless microfluid platform for 3 weeks (Abaci et al 2015 ) Validated 3D Skin comet assay with Mitomycin C; Cadmium chloride; N -ethyl- N -nitrourea; 7,12-dimethylbenz(a)thracene; Propyl gallate; Eugenol; Di-(2-ethylhexyl)phthalate; Cyclohexanone over 48 h in static environment (Reisinger et al 2018 ) Measured metabolite formation and genotoxicity after (chronic) 2-acetylaminofluorene exposure for 48 h in static environment (Downs et al 2021 ) Immortalized, i.e., HaCaT, hTERT immortalized primary cells and cocultures higher barrier property than RHE model (thus more suitable for permeation studies) Addition of fibroblasts essential for wound healing studies Culture of 2 weeks was demonstrated Still lower barrier property than in vivo HaCaT show lower metabolism than primary cells Measured caffeine, salicyclic acid and testosterone skin permeation in model containing N/TERT–keratinocytes with primary fibroblasts in microfluid permeation array for 2 weeks (Alberti et al 2017 ) iPSC-derived Can be potentially be differentiated into all cell types in the skin High proliferative capacity Stratum corneum-like structure was not readily observed (= leaky barrier) Time and cost intensive Metabolic capacity not assessed Only performed static Measured the skin permeation of 5(6)-carboxyfluorescein and fluorescein isothiocyanate dextran 4000 over 360 min in model containing iPSC-derived keratinocytes and fibroblasts in static environment (Naito et al 2019 ) Pigmented reconstructed human skin Primary cells and co-cultures Retain many morphological and signalling properties of In situ skin Model for phototoxicity, sun-related effects and vitiligo pathogenesis Lower growth rate than primary keratinocytes (can lead to either hypopigmentation or scattered pigment patches) Inter individual variations highly likely Only performed static Does not meet acceptance criteria for OECD guideline Measured impact of UV radia...…”
Section: Application Of Skin-on-a-chip In Next-generation Risk Assess...mentioning
confidence: 99%